Postovka Falco tinnunculus, sraka Pica pica - Šere, Dare (Acrocephalus, 1997)
Two nests only a metre apart, but the upper one with a roof occupied by Kestrel, on 21 May 1994 at Ljubljansko barje
Keywords: Common Kestrel; Ljubljansko barje; Magpie; opazovanje; ornithology; ornitologija; postovka; Slovenia; sraka